Eficiência agronômica do fosfato natural de Bonito, MS, em milho, braquiária ruziziensis e feijoeiro comum - Freitas, Roberto José de (2020)
Cerrado agriculture is highly dependent on the intensive application of fertilizers, given the natural conditions of low fertility of its soils. The correction and phosphate fertilization in particular constitute essential and costly operations, in view of the low availability and high adsorption of P in these soils, due to its high acidity and oxydic mineralogy. In addition, Brazil is highly dependent on the import of this nutrient, making wide use mainly of industrialized P sources with high solubility in water and high cost. Reactive natural phosphates are interesting technical and economic alternatives for application in these soils, also being provided for phosphate fertilization in agroecological production systems, where the use of industrialized soluble phosphates is not certified. The agronomic characteristics of these fertilizers are low solubility in water, presenting slower release of the nutrient. Most Brazilian phosphate reserves are of magmatic origin, with structure of non-weathered crystals, presenting very low efficiency if not industrially processed. Recently it was prospected and entered the process of mining in Bonito-MS, phosphate reserve of sedimentary origin, with P contents of the order of 20%, with great potential as a corrective source remineralizing the soil in this element. The objective of this work was to evaluate the agronomic efficiency of this natural phosphate of Bonito (FNB), compared to the natural phosphate of Morocco (FNM) and triple superphosphate (STP), applied in no-tillage of corn, intercropping with brachiaria ruziziensis and with successive cultivation of beans, in a cultivation model used in the recent crop-livestock integration systems, allowing to observe immediate and residual effects of the application. An experiment was installed in an area of the Agronomy School of UFG, with application in the fnb planting furrow at the doses of 45, 90,180 and 360 kg P2O5 ha-1 and 90 kg P2O5 ha-1 from the STP and FNM sources. The fertilization was carried out in spaced grooves of 50 cm, where corn was planted and sown to the pitch of brachiaria ruziziensis, also making sequential cultivation of beans. There were significant responses to fnb doses in grain yield and leaf terrors of Corn and bean P, in the dry matter production of brachiaria, as well as in the increase of soil P availability, demonstrating that the FNB is an efficient source of P for fertilization and soil correction in the Cerrado. The FNB showed lower efficiency than the SFT in the production of corn grains and equivalent efficiency in the dry matter production of brachiaria and common bean grains. Its efficiency was similar to that of the FNM.